THE DEVELOPMENT STRATEGY FOR PROCESSING “OTAK-OTAK” OF KURISI FISH (Nemipterus nematophorus) PRODUCTS IN UMKM MONIKA RASA, TEGAL CITY, CENTRAL JAVA - Nadhifah, Nasya Nurmalia; Zakiyah, Ratna Rizqi; Berlian, Tasha Putri; Amalia, Ayu Rizki; Priyadi, Hermawan Gatot (Politeknik Kelautan dan Perikanan Dumai, 2023)
Fish is a food product that spoils easily if the processing is not done directly, quickly, and precisely. The quality of fish needs to be maintained and handled well so that it becomes a processed food product that has added value. One fish that is quite popular is the kurisi fish which is an economical type of demersal fish. The nutritional content of kurisi fish is quite high, around 16.85% and low in fat, namely around 2.2%. Kurisi fish has a high protein content so it can be processed into a fisheries diversification product, namely otak-otak. The aim of this research is to determine the process of processing otak otak using raw materials of kurisi fish (Nemipterus nemotophorus) qualify organoleptic quality requirements so that it can be ensured that the final product of the process qualify standards and suitable for consumption. The data collection methods are active participant observation and interviews. The parameters of this research are organoleptic and sensory tests. The results of the research show that the organoleptic value of fresh fish at UMKM Monika Rasa is 8 and based on yield calculations, the average value of the final product is 154%. The organoleptic or sensory test for the otak-otak product was 8, which means that consumers like the otak-otak product very much. Product development strategies include increasing the use of appropriate technology and improving the quality of the workforce.